Tinjauan Peningkatan Prasarana dan Pariwisata atas Perubahan Komunikasi Sosial Masyarakat: Studi Kasus: Desa Cipambuan Babakan Madang, Kabupaten Bogor - Sutopo, Sutopo; Riadi, Dicky Bachtiar; Diva, Muhammad; Hanif, Luqman; Rifqi, Abu; Nugraha, Fajar (Departemen Komunikasi dan Penyiaran Islam, 2024)
This Article investigates the change process in social communication interactions in Cipambuan village through infrastructure improvements and tourism around Sentul City. The research used a qualitative approach and conducted interviews with residents. This research focuses on the keywords: Interaction, Social contact, and social communication. The results showed that improving infrastructure and tourism in Sentul town has led to significant changes in social interaction among Cipambuan villagers. The findings highlight that better infrastructure has facilitated better social contact and communication practices among residents. This research contributes to understanding how local development initiatives can impact social dynamics and relationships in rural communities. The insights gained from this research can inform future development planning and strategies to ensure sustainable social interactions and community engagement in the same context.